Pengaruh Penggunaan Fly Ash dan Fiber Glass Terhadap Kuat Tekan dan Penyerapan Air Mortar Untuk Batako - Vincensius Marvin; Anang Kristianto (Jurnal Konstruksi, 2025)
The construction industry continues to evolve with increasing demands for materials that possess high mechanical performance and are environmentally friendly. Fly ash and fiberglass are two materials with the potential to improve the quality of mortar used in concrete blocks. This study aims to analyze the optimization of compressive strength in concrete blocks through the use of fly ash as a cement substitute and the effect of fiberglass in mortar on compressive strength and water absorption. Fly ash is used as a partial cement replacement to reduce the environmental impact of the cement industry, while fiberglass is added as a reinforcement material to enhance the mechanical properties of the mortar. The method employed is a laboratory experiment, with variations in fly ash composition of 0%, 20%, and 30%, and fiberglass at 0%, 5%, 10%, and 15%. Tests were conducted to evaluate compressive strength and water absorption at 28 and 56 days. The results showed that the addition of fly ash and fiberglass significantly increased the compressive strength of the mortar. At 28 days, compressive strength increased by up to 22.5% with a composition of 30% fly ash and 10% fiberglass compared to mortar without any additives. At 56 days, the increase in compressive strength reached 27.8% with the same composition. Additionally, water absorption decreased by 18.4% with a mixture of 30% fly ash and 15% fiberglass, indicating that the combination of these two materials can reduce mortar porosity. This study contributes to the development of environmentally friendly materials in the construction industry that can reduce reliance on conventional cement and improve material efficiency. By utilizing fly ash, a by-product of coal combustion, and fiberglass as a reinforcing material, the findings support sustainable development in the production of stronger, more durable concrete blocks with a lower environmental impact.